Some Refinements of Existence Results for SPDEs Driven by Wiener Processes and Poisson Random Measures. (25th December 2012) - Tappe, Stefan
Abstract : We provide existence and uniqueness of global (and local) mild solutions for a general class of semilinear stochastic partial differential equations driven by Wiener processes and Poisson random measures under local Lipschitz and linear growth (or local boundedness, resp.) conditions. The so-called "method of the moving frame" allows us to reduce the SPDE problems to SDE problems.